How is The Application of Effective Punishment to Improve Achievement of Elementary School Students During the Covid-19 Pandemics? - Mamnun, Mamnun; Iswara, Prana Dwija (International Conference on Elementary Education, 2021)
This research was caused by teacher's complain about learning at school which was ignored by students during the Covid 19 pandemics. The purpose of this research is to give the contribution of Education punishment to students so that increases learning achievement. Participants were 55 students of elementary school from Bandung city, Cirebon regency, and Cirebon city, West Java province. Test and non-test instruments were used through the design of a quasi-experiment with a control group of pretest-posttest nonequivalent. Using a one-way ANOVA as a technical analysis of the data. The results showed that the factor without being given physical punishment was smaller than 0.05 i.e. (0.005). Learning without punishment with physical punishment was smaller than 0.05 i.e. (0.009). Lessons given Written Punishment with physical punishment were higher than 0.05 i.e. (0.953). Thus, the punishment is still effectively applied in learning activities even with the online system during the Covid-19 pandemics.